2022
DOI: 10.1002/joa3.12713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID‐19 lockdown on arrhythmias in patients with implantable cardioverter‐defibrillators in southern Italy

Abstract: Background:The effects of lockdown on non-COVID patients are varied and unexpected. The aim is to evaluate the burden of cardiac arrhythmias during a lockdown period because of COVID-19 pandemics in a population implanted with cardiac defibrillators and followed by remote monitoring. Methods:In this retrospective, multicentre cohort study, we included 574 remotely monitored implantable cardioverter defibrillator (ICD) and cardiac resynchronization therapy-defibrillator (CRT-D) recipients implanted before Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In studies from 3 separate regions in Italy, Malanchini et al [3], Sassone et al [4], and Zorzi et al [5] reported no change in ventricular arrhythmia burden and ICD therapies during the COVID-19 pandemic, disputing a higher incidence of cardiac arrests in the same period in Italy. However, Ducceschi et al [6] reported an increase in both ventricular and atrial tachyarrhythmias during the pandemic in the Campania region of Italy. In Germany, Hauck et al [7] reported no change in cardiac arrhythmias in ICD patients enrolled in a clinic, but Rath et al [8] reported an increase in cardiac arrhythmias in ICD patients during the second wave of the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…In studies from 3 separate regions in Italy, Malanchini et al [3], Sassone et al [4], and Zorzi et al [5] reported no change in ventricular arrhythmia burden and ICD therapies during the COVID-19 pandemic, disputing a higher incidence of cardiac arrests in the same period in Italy. However, Ducceschi et al [6] reported an increase in both ventricular and atrial tachyarrhythmias during the pandemic in the Campania region of Italy. In Germany, Hauck et al [7] reported no change in cardiac arrhythmias in ICD patients enrolled in a clinic, but Rath et al [8] reported an increase in cardiac arrhythmias in ICD patients during the second wave of the COVID-19 pandemic.…”
mentioning
confidence: 99%